Essay on internationalisation potential of Northwest Russian and Finnish energy clusters - Pavel Filippov; Vlad Yurkovsky (The Research Institute of the Finnish Economy (ETLA), 2007)
Finnish and Russian energy clusters widely use resources and competences of each other. They can be considered as a good example of broader phenomenon which is internationalisation of clusters. Though these clusters are on very different development stages their internationalisation ambitions, geographical proximity and complementary resources encourage them to ooperate closely, and the scale of this cooperation is predicted to grow. The article investigates the current status of the concrete energy clusters cooperation, summarises the main reasons, benefits and barriers for their cooperation, and imposes some theoretical and practical questions related to internationalisation of clusters in general.
Keywords: L14; L24; F15; F21; 330; cluster; Northwest Russia; energy; international cooperation; Energiewirtschaft; Energiepolitik; Clusteranalyse; Internationale Zusammenarbeit; Finnland; Russland (Nordwest)